Aplicación del cuento como método lúdico para el descubrimiento de nuevos conocimientos en niños de cuatro años de la Institución Educativa Inicial N° 757 Santo Cristo de Bagazán, Belén, Iquitos 2023 - Del Aguila Romayna, Jakeline Gissela (2024)
The general objective of this research is to know how the story as a playful method is related to the discovery of new knowledge in four-year-old children of the Initial Educational Institution No. 757 – Santo Cristo de Bagazán in the district of Belén, the city of Iquitos, 2023. The research had a quantitative approach, oriented to the type of descriptive research and correlational design, in a population of 200 participants of which we worked with 86 participants with a margin of error of 8% of the population total, using observation as a technique and an observation sheet as an instrument prepared by the researchers and validated by expert judgments. In the aforementioned research, it was possible to statistically demonstrate the level of application of the story as a playful method is good, as well as the level of discovery of new knowledge in four year-old children is good, it was also possible to establish that the study variables are significantly related, demonstrating that the application of the story as a playful method helps the discovery of new knowledge, the goodness of fit test was applied to the normality according to Kolmogorov-Smirnov, where the p_value of the variables application of the story as a playful method and the discovery of new knowledge have free distribution (p < 0.05), then for the inferential analysis the non-parametric statistical test Spearman's rho (rs) the same as the test statistic, Student's t with n-2 degrees of freedom. The research concludes by stating that the development or application of the story as a playful method in the discovery of new knowledge in four-year-old children is important because it helps to strengthen reading comprehension, as well as to textualize new stories taking into account the structure with which account. Finally, it is recommended to continue efficiently developing the process of applying the story as a playful method on a permanent basis, to efficiently develop the discovery of new knowledge in four-year-old children, strengthening the abilities and skills of students at this age.